Perencanaan Strategis Kantor Urusan Agama Kecamatan Ciracap dalam Optimalisasi Pelayanan Wakaf sebagai Instrumen Dakwah Pemberdayaan Umat - Mahmud, Mahmud; Saepulloh, Uwoh; Iwan Setiawan, Asep (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
Waqf when viewed from the Islamic social aspect has the aim of realizing social welfare. However, this goal is sometimes not well realized due to obstacles in realizing this goal. This study aims to describe KUA Forecasting, Establishing Objectives, Scheduling, and Budgeting in order to answer the question of how KUA planning in an effort to improve waqf service programs at the Ciracap District KUA. The method used is descriptive method with qualitative approach. The results showed that KUA planning in improving waqf service programs at the Ciracap District KUA has been carried out well, by following steps such as, the KUA forecasting stage is carried out using demand forecasting, demand forecasting, qualitative forecasting and market survey techniques in collecting data. Establishing objectives follows George T. Doran’s SMART goals method and is not set unilaterally. Scheduling is set by considering the situation and conditions of the community, and finally budgeting is set by considering previous financial reports so that program budgeting can be arranged as well as possible.